Will the Developing World’s Growing Middle Class Support Low-Carbon Policies? - Kahn, Matthew E.; Lall, Somik (World Bank, Washington, DC, 2022)
As billions of people in the developing world seek to increase their living standards, their aspirations pose a challenge to global efforts to cut greenhouse gas emissions. The emerging middle class is buying and operating energy intensive durables ranging from vehicles to air conditioners to computers. Owners of these durables represent an interest group with a stake in opposing carbon pricing. The political economy of encouraging middle class support for carbon pricing hinges on offsetting its perceived negative income effects. Rising environmentalism in the developing world could also increase support for credible greenhouse gas reduction policy. This paper quantifies these effects by estimating Engel curves of durables ownership, comparing the grid’s carbon intensity by nation, and studying the demographic correlates of support for prioritizing environmental protection.